Identification of Candida albicans Fungi in the Urine of Pre-Menstrual Girls Aged 10-14 Years at SMPN 1 Ciamis - Undang Ruhimat; Nailah Ghaissani Dwi Gustari; Firda Yanuar Pradani (Mukhtabar Journal of Medical Laboratory Technology, 2025)
Background & Objectives: Candida albicans is an opportunistic commensal fungus that becomes pathogenic when there is an immune disorder or physiological change. The resulting infection, called candidiasis, is acute or subacute and can affect various organs. Poor personal hygiene is a predisposing factor, especially in genital infections. This study aims to determine the presence and prevalence of Candida albicans in the urine of premenstrual girls aged 10-14 years at SMPN 1 Ciamis. Method: This study used a descriptive cross-sectional design. Sampling was performed using purposive sampling, with a total of 23 samples collected. The samples were examined at the Parasitology Laboratory of STIKes Muhammadiyah Ciamis. Results: The results of the study of 23 samples found 3 samples (13%) positive for Candida albicans, 2 samples (9%) positive for Candida tropicalis, and 18 samples (78%) showed no fungal growth. Conclusion Based on the results of this study, poor personal hygiene can influence Candida albicans fungal infection, especially in premenstrual adolescent girls aged 10-14 years.